English as a Lingua Franca for EFL Contexts - García Cuevas, Sara (Pulso. Revista de educación, 2019)
Reseña del libro:  Sifakis, Nicos C., and Natasha Tsantila. English as a Lingua Franca for EFL Contexts. Bristol: Multilingual Matters, 2013.